The Impact of Differentiated Problem-Based Learning on Elementary Mathematical Thinking and Problem-Solving - Dyah Kusumasari; Sendi Ramdhani; Novi Andri Nurchayono (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2026)
This study examines the effect of differentiated Problem-Based Learning (PBL) on critical thinking and mathematical problem-solving abilities among sixth-grade elementary students. These competencies are essential in today's global world yet remain inadequately taught in basic education. Using a quasi-experimental pretest-posttest control group design with cluster random sampling, the research was conducted at SDN Kutisari I/268 Surabaya for the 2025/2026 school year. The study involved 31 students in Class 6A (experimental group receiving differentiated PBL) and 31 students in Class 6C (control group receiving expository learning). Primary data came from pre-tests, post-tests on critical thinking and mathematical problem-solving, and observation sheets; secondary data from official documents. Research instruments underwent validity testing using Pearson's Product-Moment correlation, reliability testing using Cronbach's Alpha, difficulty level testing, and discriminating power index testing, analyzed via SPSS version 29. Data analysis employed the Shapiro-Wilk, Levene test, initial ability equivalence test, Mann-Whitney test, and Spearman’s Rank correlation. Findings reveal the experimental group achieved higher average post-test scores in critical thinking (80) and mathematical problem-solving (79), surpassing the control group’s scores of 74.9 and 73.3, respectively. The study concludes that differentiated PBL is more effective than expository teaching in enhancing these abilities. Results also indicate a positive relationship between critical thinking and problem-solving skills, suggesting mutual developmental support.